Pengaruh Madu dari Jenis Lebah yang Berbeda Terhadap Maskulinisasi Ikan Cupang (Betta sp.) - Al Hasan, Haifar Amru Zein; Waluyo, Waluyo; Mujtahidah, Tholibah (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
Betta fish (Betta sp.) is an ornamental fish that is in great demand by ornamental fish lovers. The characteristics and features of male Betta fish have a higher economic value than female Betta fish. One way to increase the number of male Betta fish to meet market demand is by masculinization. Fish masculinization strategies can be carried out by administering synthetic androgen hormones in the form of 17α-methyltestosterone (MT). Masculinization of fish using MT shows success in fish in increasing the number of male individuals compared to without hormone administration. The use of the synthetic hormone 17α-methyltestosterone has been prohibited in aquaculture activities because it is difficult to degrade naturally and has the potential to pollute the environment. Several other ingredients that can be used as alternatives to replace synthetic hormones are honey. This research uses honey from different types of bees with the aim of getting the best results for the percentage of male Betta fish in masculinization efforts. CRD research method (Completely Randomized Design) with 3 treatments and 4 replications. The treatments applied were T1 (Apis cerana), T2 (Apis mellifera), T3 (Trigona sp.). The best treatment was T3 (Trigona sp.) which had an effect and was very significantly different with a male percentage of 82,63 % followed by T2 (Apis mellifera) which had an effect and was not significantly different with a male percentage of 71,06 %, and T1 (Apis cerana) had an effect. and not significantly different from the male percentage of 64,45 %.